Titania nanostructures: a biomedical perspective. Issue 47 (27th May 2015) - Damodaran, Vinod B.; Bhatnagar, Divya; Leszczak, Victoria; Popat, Ketul C.
<x xml:space="preserve">Abstract</x> A systematic and comprehensive summary of various TNS-based biomedical research with a special emphasis on drug-delivery, tissue engineering, biosensor, and anti-bacterial applications.